Motivation as A Stimulus for Developing Self-Confidence in Children with Special Needs - Ariyono Setiawan; Anti Manaricha; Dwi Yanti Margosetiyowati; Ni Made Ika Marini (Jurnal Pendidikan : Riset dan Konseptual, 2023)
Motivation is the drive to do something that comes from within or from outside the self to achieve a certain goal. Self-confidence can be formed from the motivation given by parents, teachers, and the surrounding environment. Motivation becomes a force in complex conditions and prepares oneself, especially a child with special needs to achieve his expectations. Surveys show that there are still many children with special needs who are not or have not been able to independently get the opportunity to develop their identity. In this study, we focused on children with special needs how to provide motivation to develop high self-confidence so that children with special needs can be more comfortable in creating and expressing themselves. The location of our research was taken at the aora inclusive skills school in Surabaya. The purpose of this study was to find out how the role of motivation to develop self-confidence in children with special needs. This training uses a descriptive qualitative research approach, where data is obtained through interviews, obervation, and documentation. There were 70 respondents, of which the principal was the informant in this study. An attempt to convince by motivating children with special needs that they are whole, unique human beings and have advantages over other normal children. It can be concluded that self-confidence can be increased by memotoivating in the form of encouragement by teachers, especially by their parents, that they can do something without help from others.